Estimation Of Mangaan Carrier Rock Volume Using Geoelectric Method In Empol Sub-Village, West Lombok Regency - Alfina Taurida Alaydrus; Suhayat Minardi; Dieni Haryati Utami (Universitas Hamzanwadi, 2020)
The research has been done using geoelectric resistivity method to estimate the volume of Manganese (Mn) carrier rock in Empol sub-village, Central Sekotong Village, West Lombok NTB. Measurements was conducted with the Wenner configuration using a Resistivity Meter G-Sound GL - 4100. Data was modeled and calculated using three software, there are Res2Dinv 3.5, Surfer 10, and Rockwork 15. The rocks that regarded as carrier mangaan is pyrolusite manganese (Mn02). The description and distribution of MnO2 can be determined from the results of 2-dimension modeling using Res2Dinv. Mn02 was detected in almost all resistivity line with value around 0,023 Wm up to 9,8 Wm. From the 3-dimension visualization processed using RockWorks 15 software, we obtained volume of pirolusit about 38,199 m3 of area 160,000 m2 and 100 m of thickness.DOI: 10.29408/kpj.v4i2.2731